Assessing the quantities of legume-based products: A dataset of conversion coefficients into a comparable dry-legume equivalent unitRecherche Data Gouv - Marine Spiteri; Lola Pedrini; Agathe Thierry; Valérie Orozco; Olivier de Mouzon; Zohra Bouamra-Mechemache (Data in Brief)
Measuring the consumption of processed foods made from a common raw agricultural ingredient requires to make quantities comparable, by converting them in raw product equivalent. This conversion also allows to compute total quantities. In the case of legumes, the challenge is to take into account a wide diversity of final products including packaged dry legumes, processed legumes and products cooked from legumes and other ingredients. While the total quantity of the final product purchased or consumed is easily available, the corresponding quantity of dry legumes used to make the final product is not.We create a dataset of technical coefficients to convert quantities of final legume-based products into dry-legume equivalent unit. For this purpose, we first list all legume-based products purchased in French retail stores from 2002 to 2019. Those products were identified in our primary data source, the Kantar Worldpanel data. Then, for each final legume-based product, we rely on information from existing food databases, literature and products labels to build a coefficient based on three intermediary technical sub-coefficients. The first sub-coefficient measures the proportion of cooked legumes used in each product. The second sub-coefficient adjusts the quantities for products that lose water during processing (such as dehydrated or baked products). Finally, the third sub-coefficient is a conversion coefficient, used to express the quantities of legumes purchased in dry-legume equivalent.This dataset centralizes technical conversion coefficients that are useful to analyze global French legume markets, regardless of the type of product purchased (dried legumes, canned legumes, meals...). These coefficients also allow to infer quantities at the upstream agricultural production level.